El Salvador Financial Sector Assessment Program Development Module : Financial Inclusion - World Bank (World Bank, Washington, DC, 2017)
This Technical Note was prepared in the context of a World Bank Financial Sector Assessment Program mission in the Republic of El Salvador in March 2016. Despite the challenging economic environment, El Salvador has made significant strides towards a more inclusive financial sector. However, El Salvador faces a number of challenges, including regulatory weaknesses and uncertainty, anti-competitive practices, and a fragile security situation that impacts investment and innovation. The country still presents low levels of access to and use of a range of financial services. The financial sector is diversified, but some challenges need to be overcome to increase competition and innovation. There seem to be no excessive legal barriers to entry for new banks and the framework allows for a diverse range of large and small deposit-taking entities. The microfinance sector is diverse and competitive and reforms are underway to strengthen regulation and supervision, but capacity is an issue. Also, the microfinance prudential regulation should be improved to be in line with international good practices and standards. Reforms are needed to spur the use of electronic accounts and transactions and to improve the draft rules for simplified accounts. Further progress could be made by allowing bank and nonbank financial institutions access to and use of telecommunications infrastructure on a non-discriminatory basis. An effective consumer protection legal, regulatory and supervisory framework is needed to ensure healthy financial inclusion. The Note contains technical analysis underpinning the FSAP findings and recommendations. Given the requested focus on digital finance and consumer protection, certain areas relevant to financial inclusion – notably small and medium enterprise finance, financial education, microfinance regulation and supervision– have been addressed in an abbreviated manner in this Technical Note. Although this Note incorporates some insights from the Technical Notes covering Financial Infrastructure, Non-Bank Savings and Credit Institutions (NBSCI) and Public Banks, not all related issues are incorporated in this Note, so the other Technical Notes should be read for a more comprehensive view of Salvadoran financial inclusion.